Metabolic Effects of Bariatric Surgery. (4th January 2020) - Sinclair, Piriyah; Docherty, Neil; le Roux, Carel W
Abstract: BACKGROUND: Obesity can be defined as a chronic subcortical brain disease, as there is an important neurophysiological component to its etiology based on changes in the functioning of those areas of the brain controlling food intake and reward. Extensive metabolic changes accompany bariatric surgery-based treatment of obesity. Consequently, the term "metabolic" surgery is being increasingly adopted in relation to the beneficial effects these procedures have on chronic diseases like type 2 diabetes. CONTENT: In the present review, we focus on the key biochemical and physiological changes induced by metabolic surgery and highlight the beneficial effects accrued systemically with the use of an organ-based approach. Understanding the impact on and interactions between the gut, brain, adipose tissue, liver, muscle, pancreas, and kidney is key to understanding the sum of the metabolic effects of these operations. SUMMARY: Further mechanistic studies are essential to assess the true potential of metabolic surgery to treat metabolic comorbidities of obesity beyond type 2 diabetes. Approaches that may mitigate the metabolic side effects of surgery also require attention. Understanding the positive impact of metabolic surgery on metabolic health may result in a wider acceptance of this intervention as treatment for metabolic, comorbid conditions.